PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN NUMERASI SISWA KELAS V DI SD NEGERI LAMPER TENGAH 01 - Cantika Ageng Maharrani; Kartinah; Henry Januar Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The investigation’s backdrop is the poor numeracy achievement of the class V students at SD Negeri Lamper Tengah 01 Semarang. The study aims to examine the extent of using the Problem-Based Learning (PBL) model can enhance numeracy skills of class V students. To achieve this objective, the study employed a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest model. The exploration population was made up of the class V students at SD Negeri Lamper Tengah 01 Semarang, with a saturated sampling of 28 scholar named using a impregnated slice fashion. The data were normally distributed with a significance value > 0.05, according to the data analysis, which showed that the average pretest score was 43.21 and posttest score was 82.32. The paired sample t-test further revealed a calculated the t-value was 13,16 and the t-table value was 2,052. Ho was rejected and Ha was accepted because the t-value was greater than the t-table. Thefore, it can be said that class V scholars at SD Negeri Lamper Tengah 01 Semarang improved their numeracy skills significantly as a result of using the Problem-Based Learning.